2017
DOI: 10.1007/s00404-017-4299-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of mode of delivery on the sexual function of primiparous women: a prospective study

Abstract: Our study revealed that caesarean section is not superior to vaginal birth in terms of preservation of normal sexual function, regardless of short-term postpartum effects. Women should be informed that, irrespective of their type of delivery, sexual function 6 months after childbirth is similar to that in pre-pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
27
2
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 36 publications
6
27
2
8
Order By: Relevance
“…In the present study, women who underwent CS had statistically significant higher FSFI than women who underwent VD, however, the difference was clinically subtle. In line with our findings, a recent prospective study on 452 nulliparous women by Kahramanoglu et al found slight differences in FSFI items between women who underwent CS and VD at 3 and 6 months postpartum. The authors concluded that the CS had no superior effect on postpartum sexual function compared to VD .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, women who underwent CS had statistically significant higher FSFI than women who underwent VD, however, the difference was clinically subtle. In line with our findings, a recent prospective study on 452 nulliparous women by Kahramanoglu et al found slight differences in FSFI items between women who underwent CS and VD at 3 and 6 months postpartum. The authors concluded that the CS had no superior effect on postpartum sexual function compared to VD .…”
Section: Discussionsupporting
confidence: 93%
“…In line with our findings, a recent prospective study on 452 nulliparous women by Kahramanoglu et al found slight differences in FSFI items between women who underwent CS and VD at 3 and 6 months postpartum. The authors concluded that the CS had no superior effect on postpartum sexual function compared to VD . Although the VD was noted to have a long‐term effect on sexual function in Doğan et al study, such effect was reported to be clinically subtle and did not lead to sexual dysfunction.…”
Section: Discussionsupporting
confidence: 93%
“…18,19 Regarding the arousal domain, a decrease in arousal with pregnancy was observed. Similar findings were observed in a cross-sectional study 20 with 181 non-pregnant women and 177 pregnant women, in which the overall sexual dysfunction rate was of 31.7%, and it was more prevalent in pregnant women (40.4%) than in non-pregnant women (23.3%), with a significant difference between them in the score of the arousal domain (p ¼ 0.003). 20 The criteria that characterize sexual dysfunction in the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV) included low sexual desire, sexual arousal disorder, orgasmic disorder and sexual pain disorder.…”
Section: Discussionsupporting
confidence: 86%
“…More women in Group 1 (32 [9.2%]) than in Group 2 (12 [4.0%]) had 3 to 4 vaginal deliveries; however, this may not be associated with a worse sexual function, as has been shown in a previous study in which no negative effect on the sexuality of women after vaginal delivery was found. 14 A prospective study evaluated 158 LNG-IUS users, in which the participants answered the FSFI questionnaire at the beginning of the survey and after 1 year of use. 8 There were no significant differences between the two moments of response to the questionnaire.…”
Section: Discussionmentioning
confidence: 99%